Thai mothers working in agriculture: Effects of heavy metal exposure on endocrine-related hormones in the neonates - Grant A. Walter (2018)
© 2016 by Nova Science Publishers, Inc. Changes in pubertal timing increase risks for adverse health outcomes. Many environmental toxicants have been shown to modulate onset of puberty. Heavy metals (HMs) have been associated with both delayed and precocious puberty but information is lacking for each HM’s mode of action (MOA). The Hypothalamic-Pituitary-Gonadal (HPG) axis controls pubertal development through release of LH initiated during fetal development. HMs hypothesized MOA for pubertal delay is modulation of HPG axis’ hormone concentration but evidence of this during fetal life is lacking. To examine this hypothesis, we used archived samples collected from 56 mother-infant dyads who participated in the Study of Asian Women and their offSpring’s Development and Environmental Exposures (SAWASDEE) cohort in Chiang Mai, Thailand. Maternal and umbilical cord blood metal concentrations were measured using ICP-MS and neonatal urine luteinizing hormone (LH) concentrations were measured using an enzyme immunoassay. Multiple logistic regression analyses were used to evaluate the relationship between maternal HM levels and neonatal LH categories ( < 0.4 mlU/mL and ≥ 0.4 mlU/mL). None of the metals tested were associated with LH categories although neonate sex was significantly associated with LH category [OR 11.53 (1.12 - 118.94), p = 0.04]. This is the first study to evaluate prenatal HM exposure in relation to infant LH hormone levels. HM exposures in this small pilot cohort do not appear to be related to LH levels.